2019
DOI: 10.21608/jappmu.2019.48275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Proanthocynidins Supplementation on Productive and Reproductive Performance of Sinai Hens from 47 to 62 Week of Age

Abstract: An experiment was designed on 165 local Sinai laying hens (150 females + 15 males), 47 wk-old, were equally divided into five dietary treatments to determine possible benefits from dietary supplementation with proanthocyanidins to the layer's diet of grape pomace and green tea extracts (GPGT extract) at levels (0, 50, 100, 150 and 200 mg/kg diet) on productive and reproductive performance during the laying period from 47 to 62 wk of age. Results illustrated that egg number/hen or laying rate (%) significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Also, incorporation of GSPE in the diet at 5, 10, 20, 40 and 80 mg/kg diet significantly increased BWG of broiler chickens after the E. tenella infection (Wang et al, 2008). More recently, Beshara et al (2019) explained that inclusion of 150 mg GPGT extract/kg diet can be used to maximize the productive performance and economic efficiency of Sinai hen's (47 -62 weeks of age). On the contrary, Hughes et al (2005) reported that BW decreased when broilers fed GSE.…”
Section: Productive Performancementioning
confidence: 99%
“…Also, incorporation of GSPE in the diet at 5, 10, 20, 40 and 80 mg/kg diet significantly increased BWG of broiler chickens after the E. tenella infection (Wang et al, 2008). More recently, Beshara et al (2019) explained that inclusion of 150 mg GPGT extract/kg diet can be used to maximize the productive performance and economic efficiency of Sinai hen's (47 -62 weeks of age). On the contrary, Hughes et al (2005) reported that BW decreased when broilers fed GSE.…”
Section: Productive Performancementioning
confidence: 99%